Pinning Effects of Exchange and Magnetocrystalline Anisotropies on Skyrmion Lattice - Wan, Xuejin; Hu, Yangfan; Hou, Zhipeng; Wang, Biao (Frontiers in Physics, 2021)
Reorientation of skyrmion crystal (SkX) with respect to crystallographic axes is believed to be insensitive to anisotropies of fourth order in spin-orbit coupling, for which sixth order terms are considered for explanation. Here, we show that this is wrong due to an oversimplified assumption that SkX possesses hexagonal symmetry. When the deformation of SkX is taken into account, fourth order anisotropies such as exchange anisotropy and magnetocrystalline anisotropy have pinning red(in this work, the word ‘pinning’ refers to the reorientation effects of intrinsic anisotropy terms) effects on SkX. In particular, we reproduce some experiments of MnSi and Fe_1-xCo_xSi by considering the effect of fourth order magnetocrystalline anisotropy alone. We reproduce the 30^° rotation of SkX in Cu_2OSeO_3 by considering the combined effects of the exchange and magnetocrystalline anisotropies. And we use the exchange anisotropy to explain the reorientation of SkX in VOSe_2O_5.